EFFECT OF PROCESS-BASED INSTRUCTION AND DISCUSSION METHOD ON SECONDARY SCHOOLS STUDENTS’ PERFORMANCE IN HEAT ENERGY IN SOKOTO STATE, NIGERIA - ALIYU, MURJANATU; DAUDA, SUFIYANU; CYRIL, MATTHEW (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
This study investigated the effect of Process-Based Instruction and Discussion method on Secondary School Students’ Performance in Heat Energy in Sokoto state, Nigeria. The study employed quasi- experimental research design involving pretest and posttests. Ten (10) schools with a total of 2264 SS II Students formed the population of the study, out of which 965 were sampled using purposive sampling techniques across gender. Four intact classes were selected from the four participating schools. The instrument titled Heat Energy Performance Test (HEPT) was used for data collection. The instrument was validated by experts and reliability coefficient of 0.89 (using KR 20) was established. Research questions were answered using means and standard deviation while research hypotheses were tested at 0.05 level of significance using t-test. The findings revealed that there was significant difference in the performance of students in experimental and control groups. No significant difference among gender in students’ performance was observed. It was recommended that stake holders in education should organize seminars and conferences for science teachers and emphasize the implementation of Process Based Instruction in the teaching of secondary school physics.